Effect of Increased Corticosterone Levels Due to Chronic Stress on Body Weight Changes in Rattus norvegicus - Risya Secha Primindari; Amrina Nur Rohmah; Dwi Dianita Irawan (MAGNA MEDIKA: Berkala Ilmiah Kedokteran dan Kesehatan, 2022)
Background: Stressors in everyday life cannot be predicted in various forms; if individuals cannot cope with exposure to stress, it causes chronic conditions. Corticosterone is a biomarker associated with chronic adaptation. Weight loss is associated with an increase in glucocorticoid hormones due to stress which affects the burning of brown fat so that calories are burned.Objective: Analyze the effect of increasing serum corticosterone levels due to chronic stress on changes in body weight of Rattus novergicus.Methods: Samples were 34 Rattus norvegicus which were divided into 2 groups, control and stress treatment using the Chronic Unpredictable Mild Stress (CUMS) method. Serum corticosterone levels were detected by ELISA examination and body weight changes were monitored twice, before and after CUMS was given.Results: Corticosterone in the treatment group was higher (72.84 ± 64.03) than the control group (23.29 ± 8.42). Changes in body weight of the control group (14.62 ± 4.98) were heavier than the treatment group (-10.33 ± 11.24). Statistical test p=0.000 (p <0.05).Conclusion: chronic stress increases corticosterone hormone levels in Rattus novergicus serum and increased levels of corticosterone hormone can reduce body weight.